Analysis and synthesis of supershaped dielectric lens antennas. Issue 14 (1st November 2015) - Bia, Pietro; Caratelli, Diego; Mescia, Luciano; Gielis, Johan
Abstract : A novel class of supershaped dielectric lens antennas, whose geometry is described by the three‐dimensional (3D) Gielis' formula, is introduced and analysed. To this end, a hybrid modelling approach based on geometrical and physical optics is adopted in order to efficiently analyse the multiple wave reflections occurring within the lens and to evaluate the relevant impact on the radiation properties of the antenna under analysis. The developed modelling procedure has been validated by comparison with numerical results already reported in the literature and, afterwards, applied to the electromagnetic characterisation of Gielis' dielectric lens antennas with shaped radiation pattern. Furthermore, a dedicated optimisation algorithm based on quantum particle swarm optimisation has been developed for the synthesis of 3D supershaped lens antennas with single feed, as well as with beamforming capabilities.